A possible Parthian-era Anahito sanctuary at Rabana in the Kurdistan region of Iraq - Brown, Michael; Rashid, Rebin (Iraq, 2023)
Rabana-Merquly was a major regional centre of the Parthian era in the central Zagros highlands. This article explores the hypothesis that the Rabana intramural settlement was in part a ‘sanctuary’ devoted to the ancient Persian water goddess Anahita, based upon extensive architectural augmentations around an ephemeral waterfall, combined with the nearby construction of a probable fire altar. Two jar burials excavated in 2022 inside an adjacent building show this complex also functioned as a mausoleum. Carbon-14 dating of these cremation deposits supports occupation of the site during the second to first centuries B.C. Twin rock reliefs at the entrances to Rabana-Merquly indicate that the fortress was likely associated with the ruling dynasty of Adiabene, a vassal kingdom of the Parthian (or Arsacid) Empire in north-east Mesopotamia. A further link to Natounissarokerta/Natounia on the Kapros is suggested by the iconography of that city's coinage, which features an obverse image of a goddess, potentially a hybrid representation of Anahita-Tyche., كانت ربانا, ميركولي Rabana-Merquly مركزًا إقليميًا رئيسيًا للعصر البارثي في هضبات زاغروس Zagros الوسطى . يستكشف هذا المقال الفرضية القائلة بأن مستوطنة ربانا كانت في جزء منها "ملاذًا" مكرسًا للإلهة الفارسية القديمة أناهيتا ؛ وذلك بناءً على اضافات معمارية واسعة النطاق حول شلال غير دائم الوجود، جنبًا إلى جنب مع بناء لمذبح ناري محتمل . وجود مدافن للجرار داخل مبنى مجاور يشير الى أنها كانت تتخذ كضريح. هذا وتدعم عملية التأريخ باستخدام الكربون -14 للعظام المتفحمة من أحد رواسب حرق الجثث التي تم التنقيب عنها في عام 2022 بأن الموقع كان مستخدما خلال القرن الأول قبل الميلاد. من المحتمل أن تكون رابانا ميركولي مرتبطة بالسلالة الحاكمة لأديابين ، وهي مملكة تابعة للإمبراطورية البارثية (أو أرسايد) في شمال شرق بلاد ما بين النهرين . وتقترح الدراسة بأن ثمة رابط آخر لنطونيا على نهر كابروس استنتج وجوده من خلال الأيقونات الظاهرة على نقودها ، والتي تحتوي على صورة وجهية لإلهة المدينة ، والتي من المحتمل أن تكون تمثيلًا هجينًا لأناهيتا- تايكي .
Online veröffentlicht: 11. Januar 2024
Gesehen am 16.08.2024